ANALISIS KETERAMPILAN PROSES SAINS MATERI KOLOID MELALUI PEMBELAJARAN BERBASIS PROYEK BERVISI SETS - Wismaningati, Putri; Nuswowati, Murbangun; Sulistyaningsih, Triastuti; Eisdiantoro, Sunarko (Universitas Negeri Semarang, 2019)
A research aimed to explore students’ science process skill of students in colloid concept through project based learning vision of SETS. This research involved 34 reseach subjects. Instrument used research is observation sheet and as supporting data student response questionnaire. The data obtained from observation sheets learning to know the science process skills developed by students and queationnaires were used to collect the students’ respond to learning. Student response questionnaire used to know student response to learning done. The data are analyzed descriptively. Results from this study showed that the students had all the indicators of science process skills a googd category with a percentage of 65.48%. Students give a positive response to learning because they feel more understanding, increase motivation and interest in learning. This is evidenced by 85% students of class XI IPA 1 SMA N 2 Purbalingga provide responses that fall into either category of learning that hs been done.